Accurate segmentation of green fruit based on optimized mask RCNN application in complex orchard - Jia, Weikuan; Wei, Jinmeng; Zhang, Qi; Pan, Ningning; Niu, Yi; Yin, Xiang; Ding, Yanhui; Ge, Xinting (Frontiers in Plant Science, 2022)
Fruit and vegetable picking robots are affected by the complex orchard environment, resulting in poor recognition and segmentation of target fruits by the vision system. The orchard environment is complex and changeable. For example, the change of light intensity will lead to the unclear surface characteristics of the target fruit; The target fruits are easy to overlap with each other and blocked by branches and leaves, which makes the shape of the fruits incomplete and difficult to accurately identify and segment one by one. Aiming at various difficulties in complex orchard environment, a two-stage instance segmentation method based on optimized Mask Region Convolutional Neural Network (Mask RCNN) was proposed. The new model proposed to apply the lightweight backbone network Mobilenetv3, which not only speeds up the model but also greatly improves the accuracy of the model and meets the storage resource requirements of the mobile robot. In order to further improve the segmentation quality of the model, the boundary patch refinement (BPR) post-processing module is added to the new model to optimize the rough mask boundaries of the model output to reduce the error pixels. The new model has a high-precision recognition rate and an efficient segmentation strategy, which improves the robustness and stability of the model. This study validates the effect of the new model using the persimmon dataset. The optimized Mask RCNN achieved mean average precision (mAP) and mean average recall (mAR) of 76.3% and 81.1%, respectively, which are 3.1% and 3.7% improvement over the baseline Mask RCNN, respectively. The new model is experimentally proven to bring higher accuracy and segmentation quality, and can be widely deployed in smart agriculture.